EDUKASI PIJAT BAYI DALAM MENINGKATKAN PENGETAHUAN IBU TENTANG TEHNIK DAN MANFAAT PIJAT BAYI - Yaumil Fauziah; Fitri Khairani (STIKES Garuda Putih, 2026)
Background: Infant massage, also known as baby massage, is a massage technique that involves gentle stroking or tactile stimulation of the skin, as well as manipulation of body tissues and organs, aimed at affecting muscle tone, the respiratory system, and improving blood circulation. It is a form of multisensory stimulation that can support optimal infant growth and development, especially when performed during the first 1,000 days of life. Infant massage is one of the oldest touch therapies known to humans and also one of the most popular. Objective: This community service activity aims to increase mothers' understanding of the importance of infant massage for their growth and development before and after infant massage therapy. Method: Education was conducted through lectures and live demonstrations at the Hadijah Medan Clinic, with the participation of 12 participants, using leaflets and flipcharts. Results: The results of this activity indicated that participants had a better understanding of the six steps of handwashing according to WHO standards, and that patients' families also had a better understanding of the risk factors that cause falls. Before participating in the training, 5 of the 12 participants (41.67%) already understood the material. After the training, all participants (100%) demonstrated adequate understanding. This represents a 58.33% increase in understanding. Participants also participated in discussions and demonstrated high levels of enthusiasm for the activity. With this training, it is hoped that infant massage techniques can be incorporated into daily life, enabling optimal infant growth and development.